(untitled) (Progressive Agriculture, 2020)
Performance of a motor operated oil palm crusher was tested at the Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh. The crusher is powered by a three- phase 7.5hp electric motor. Crushing efficiency and crushing capacity are some of the most important parameters for evaluating the crushing performance. This study provides some information on the composition of crude palm oil, palm oil extraction methods, the crushing efficiency, etc. The crusher has an average oil extraction efficiency of 72.84 %. This was obtained from 2.5kg of palm fruit at the steaming time of 2min. The average crushing capacity of the crusher was 12.72 kg/hr. The average crude palm oil percentage in fruit was 19.67%. On an average 200 gm of crude palm oil was extracted from 1 kg of fruit. The average oil cake percentage in palm fruit was 62.2% and the average sediment percentage was 14.04%. Manually, the crushing capacity was 0.84 kg/hr, crude palm oil percentage was 22.14%, oil cake percentage was 44.28%. The break-even point of the crusher was 700 hr. It means that if the crusher is used for more than 700 hr, it will be economically suitable compared to manual crusher. The quality parameters evaluated were Free fatty acid, Iodine value, Peroxide value and Saponification value. Free fatty acid was 1.33%; Iodine value was 50; Peroxide value was 2meq/kg; and Saponification value was 120. Overall performance of the machine was satisfactory compared to manually operated crusher. Progressive Agriculture 30 (3): 317-327, 2019